Precipitation hardening and structure evolution in hypereutectic Al-6 % Fe-Zr alloys subjected to ultrasonic melt processing - S. Chankitmunkong; F. Wang; P. Pandee; C. Limmaneevichitr; D.G. Eskin (My University, 2023)
The objective of this research was to study the influence of Zr concentration and ultrasonic melt processing (USP) on the microstructure and precipitation hardening of a hypereutectic Al-6% Fe alloy. Such alloys have a good potential in high-temperature, wear-resistant, and conducting applications but suffer from coarse structure and low strength/ductility, which prevents their processing. The microstructure of the studied alloys consisted of primary Al13Fe4 intermetallics and (Al)+Al13Fe4 eutectic colonies, which were successfully refined by adding Zr and performing USP. The mechanisms of USP and Zr were confirmed for the Al-6% Fe alloys with a range of Zr additions. The structure refinement led to improved hardness and tensile properties of the alloys. All studied alloys demonstrated strong precipitation hardening effect with hardness increasing 4-5 times, reaching 170 HV for the alloy with 0.4% Zr after annealing at 400 ℃ for 20 hrs. The electrical conductivity increased from 20% IACS in as-cast alloy to 40% IACS in the annealed Al-6% Fe-0.4% Zr alloy. The prime novelty of this work is a considerable increase of hardness upon annealing, i.e. more than 100 HV, in the Al-6% Fe alloy with only minute traces of Zr (<0.01%). The precipitation phenomena were investigated by transmission electron microscopy. The precipitation of the semi-coherent Al13Fe4 phase with Zr segregated to its surface was observed for the first time. All studied alloys (with minute and larger Zr additions) showed the precipitation of this phase, while the alloys with the larger amount of Zr also demonstrated the precipitation of the metastable L12 Al3Zr phase. Therefore, the properties improvement was attributed to the structure refinement and the formation of Zr-modified Al13Fe4 and Al3Zr precipitates in the microstructure.
Keywords: Precipitation hardening; Hardening (computing); Aluminum Alloy Microstructure Properties